Structural Feature of Adducts of Tin(II) Chloride with Thiosemicarbazone Derived from 2-Pyridinecarboxaldehyde and p-Anisaldehyde - Raizada, M.S. (Asian Journal of Chemistry, 2010)
Equimolar reactions of tin(II) chloride with thiosemicarbazonesand 4-phenylthiosernicarbazones in anhydrous tetrahydrofuranunder nitrogen atmosphere resulting in the isolation of a new seriesof tin(II) adducts formation of the type SnCI2·L (where L =thiosernicarbazones or 4-phenylthiosemicarbazones of 2-pyridinecarboxaldehydeand p-anisaldehyde). The IR and 1H NMR spectralstudies indicate coordination of tin to the azomethine nitrogen andsulphur of the ligand moiety.